Experimental analysis of machining performance based on selected cutting parameters for smart CNC turning environment - Shuhaidi Mohamad, 1981- author; Aini Zuhra Abdul Kadir, supervisor; Fakulti Kejuruteraan Mekanikal (2014)
Thesis (Sarjana Kejuruteraan (Mekanikal - Teknologi Pembuatan Termaju)) - Universiti Teknologi Malaysia, 2014